The Use of Magic in the Village Head Election in Tidore Islands City Indonesia - Rosyidi, Irham; Faisal, Fatma; Umar, Mahmud Hi; Sybelle, Jan Alizea; Junaidi, M (Universitas Semarang, 2024)
In Indonesia, the Village Head Election is the implementation of people’s sovereignty to choose village heads in a direct, public, free, confidential, honest, and just manner as stated in Regulation of the Minister of Internal Affairs No. 27 of 2020. This paper aims to analyze deviant behavior in the Village Head Elections that may bring harm to other people that involve the role of supernatural beings committed by Village Head Election participants. The importance of learning magic for the Village Head Election includes: (1) to influence the opinion of society who have suffrage rights; (2) to manipulate the obtainment of votes; (3) to make other Village Head Election participants die and/or sick; and (4) to influence the opinion of Village Head Election organizers. This paper employed the juridical empirical research method in the field of the legal anthropology scientific discipline. It used the behavioral approach. This paper aims to understand how mystical practices may influence election results that should ideally be carried out in a just and honest manner as well as to increase awareness of the risk of unethical behavior in the election process. Results showed that mystical things are always closely related to the culture of the Indonesian nation from era to era, including in its political culture. It can be seen that in every leadership of national figures, mystical activities are practiced. Contestants will visit shamans by sending voodoo to their political opponents so that they can win the political contestation. Apart from that, there are those who carry out rituals that are believed to be effective as a way to win the contestation in the political realm. The novelty of this research is that authors not only analyze the magical aspect of the Village Head Elections but also how magic is believed and implemented at the national level. The implication of this case is that it is rather difficult to prove magical cases. Thus, it leads to the occurrence of widespread suspicion among all parties.